Sumbangan Sheikh Sa’id Hawwa (1935-1989): sorotan awal proses tazkiyah al-nafs sebagai wadah pembersihan jiwa - Nur Zainatul Nadra Zainol (TERAJU: Jurnal Syariah dan Hukum, 2019)
Tazkiyah al-nafs is a method of purification of the human soul in the form of internal purification and external formation in order to suppress desires and bad habits that lead to mental health and behavioral disorders. Sufism figures have introduced the method of purification of the soul, including Sheikh Sa'id Hawwa, which further explains Imam al-Ghazali's method of purification of the soul. This article aims to highlight the contribution of this figure in this field and analyse the approach presented by Sheikh Sa'id Hawwa in the method of tazkiyah al-nafs. This study is a qualitative study with content analysis design. The results show that Sheikh Said Hawwa has highlighted the method of tazkiyah al-nafs that is able to educate the human soul to avoid mental health and behavioral disorders. This study can provide early guidance and highlights on the method of purification of the soul based on the Quran and al-sunnah